Hubungan Pengetahuan Dengan Kejadian Kekurangan Energi Kronis (KEK) Pada Ibu Hamil Di Wilayah Kerja Puskesmas Air Tiris Kabupaten Kampar Tahun 2023 - Kalsum, Ummi; Harahap, Dewi Anggriani; Syahda, Syukrianti (Evidence Midwifery Journal, 2024)
Chronic Energy Deficiency (KEK) is one of the nutritional problems experienced by pregnant women. Pregnant women with CED will have negative effects both on themselves and the fetus they are carrying. In 2020, reported that the prevalence of CED in global pregnancies was 35-75%, WHO also recorded that 40% of maternal deaths in developing countries were related to CED with the highest prevalence. Risk factors for mothers experiencing CED during pregnancy are risks and complications for the mother, including anemia, bleeding, not gaining weight normally, infectious diseases. This research aims to determine knowledge about the incidence of CED in pregnant women in the Air Tiris Health Center Work Area in 2023. This type of research is quantitative research using an analytical survey method with a cross sectional approach. The population in this study was all pregnant women at the Air Tiris Health Center in 2023, totaling 723 people using a random sampling technique of 257 people. Data collection uses a master table. The data analysis used was univariate and bivariate analysis with the Chi Square test. The results of the univariate analysis showed that 111 (42.7%) mothers had less knowledge. The results of the Chi Square test show a relationship between knowledge and the incidence of chronic energy deficiency in pregnant women (p value = 0.001) at the Air Tiris Health Center in 2023. The suggestion of this research is to minimize the incidence of CED and improve health services even better by providing counseling to pregnant women to prevent CED during pregnancy. It is hoped that health workers will use the results of this research as a reference in creating programs to increase education by health workers for mothers regarding good maternal knowledge during pregnancy